Unique challenges posed by a dysfunctional native right ventricular outflow tract for percutaneous pulmonary valve implantation using SAPIEN-S3 valve - Kothandam Sivakumar; Ramyashri Chandrasekaran; Ziyad M Hijazi (Wolters Kluwer Medknow Publications, 2022)
Dysfunctional right ventricular outflow tracts after a repair for tetralogy of Fallot using a transannular patch offer limited nonsurgical opportunities due to their large dimensions. A discrete subannular narrowing between a dilated right ventricle and the enlarged pulmonary trunk was a potential anatomical target for the creation of a landing zone using a prestent in a young male with severe pulmonary regurgitation and moderate stenosis. Asymmetric expansion of the prestent in the angulated outflow tract led to distal stent embolization that was stabilized by another telescoping stent before successful valve implantation. This manuscript details the unique challenges posed by a dilated regurgitant outflow tract for implanting a pulmonary valve.